CORRELATION OF SOIL NUTRIENTS WITH ZOOBENTHOS IN GROUND PEAT POND THAT WERE GIVEN BIOFERTILIZER FORMULATION - Rahmayuni, Apriliza; Hasibuan, Saberina; Syafriadiman, Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstrack This research was conducted from May until July 2018 at the Kualu Nenas village, Tambang Subdistrict, Kampar Regency, Riau Province. The objective of this was to study to determine opportune biofertilizer formulation, correlation of soil nutrient with zoobenthos in ground peat pond that were given biofertilizer formulation. The method used in this study is an experimental method using a Complete Random Design (CRD) with 1 factor, 5 treatment and 4 replications. The treatment used in this experiment are P0 (control/non biofertilizer formulation), P1 (biofertilizer formulation 700g/m2), P2 (biofertilizer formulation 750g/m2), P3 (biofertilizer formulation 800g/m2), P4 (biofertilizer formulation 850g/m2). Result of this study shown that the best treatment was P2 (biofertilizer formulation 750g/m2) were a N 0,81%, P 0,16%, K 0,84%, KBOT 76,81%, microzoobenthos abudance 62.172 ind/m2 and macrozoobenthos abudance 30.581 ind/m2. The analysis of the KBOT showed strong correlation with zoobentos abudance. The parameters of water quality such as water temperature ranged between 27,94-30,14 ; pH 6-7; DO 3,06-3,70ppm; nitrates 1,72-2,87ppm and orthoposfat 1,76-3,30 ppm. Absolute weight, absolute length growth and specific growth rate of Patin fish is 3,31grams; 5,25cm; 98,75% respectively. Keywords: Biofertilizer formulation, Microzoobenthos, Macrozoobenthos